2002
DOI: 10.1248/bpb.25.923
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Dose of Omeprazole for CYP2C19 Extensive Metabolizers in Anti-Helicobacter pylori Therapy: Pharmacokinetic Considerations.

Abstract: Proton pump inhibitors are occasionally used in therapy for eradicating Helicobacter pylori in the combination with antimicrobials, [1][2][3][4][5] for the prevention of gastric and duodenal ulcer diseases.1,2) Triple therapy using omeprazole, amoxicillin, and clarithromycin is now recommended for anti-H. pylori therapy because of its high eradication rate (greater than 90%), [3][4][5] although problems with this therapy have arisen including the resistance of H. pylori to clarithromycin by failure. 2,3)Omepra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 22 publications
(35 reference statements)
0
29
0
Order By: Relevance
“…Plasma PPI levels and intragastric pHs during PPI treatment in the RM group are lowest, those in the IM group come next, and those in the PM group are highest among the three groups. Eradication rates with triple therapy are inversely related to the ability to metabolize the PPIs (ie the RM group has lower eradication rate compared to other groups) 30,[33][34][35][36][37][38] .…”
Section: Host Factors Influencing Treatment Successmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma PPI levels and intragastric pHs during PPI treatment in the RM group are lowest, those in the IM group come next, and those in the PM group are highest among the three groups. Eradication rates with triple therapy are inversely related to the ability to metabolize the PPIs (ie the RM group has lower eradication rate compared to other groups) 30,[33][34][35][36][37][38] .…”
Section: Host Factors Influencing Treatment Successmentioning
confidence: 99%
“…Studies are needed in Western populations to confirm the success seen in Japan and to identify the dose and doing intervals of each PPI to ensure the best effect. Clinical trials have suggested that approximately 80 mg of omeprazole given every 12 hours was sufficient 36 . Clinical studies with every 6 hour dosing have proven successful in Japan 51,68 .…”
Section: Dual Therapy and Dual Therapy-based Special Therapiesmentioning
confidence: 99%
“…The clinical consequences of the CYP2C19 gene polymorphisms have not been fully understand but can be illustrated with the case of proton-pump inhibitors. The EMs metabolizes these drugs at a speed that requires doses up to four times greater than PMs to reach similar serum concentrations and effects [12,13]. …”
Section: Introductionmentioning
confidence: 99%
“…A series of clinical studies on the CYP2C19 genotype and the pharmacokinetics and pharmacodynamics of three proton pump inhibitors (PPIs), omeprazole, lansoprazole and rabeprazole, were conducted to establish the individualized pharmacotherapy based on the CYP2C19 genotyping. [1][2][3][4][5] The subjects were classified into homo extensive metabolizers, hetero extensive metabolizers and poor metabolizers according to the CYP2C19 genotype diagnosed. The findings were summarized as follows: 1) plasma concentrations of omeprazole and lansoprazole after single oral administration were defined by the CYP2C19 genotype, whereas rabeprazole was not, 2) the CYP2C19 genotype-dependency of lansoprazole was weaker than omeprazole, and 3) hetero extensive metabolizers could be included with homo extensive metabolizers to be extensive metabolizers.…”
mentioning
confidence: 99%